Pengembangan Soft Skills dan Character Building bagi Mahasiswa Manajemen Agribisnis Menuju SDM Unggul - Pristiwaningsih, Estin Roso; Rizky, Dian; Maghfiroh, Canggih Nailil; Firmansyah, Akbar Maulana (Neolectura, 2024)
In the era of global competition, the agribusiness sector requires human resources which have technical competencies and good soft skills and character. This community service program aims to enhance communication skills, leadership, teamwork, critical thinking, and work ethics among Agribusiness Management students through an experiential learning approach. The methods used include simulation-based training, focus group discussions (FGDs), and mentoring by academics and agribusiness practitioners. Evaluation results from pre-tests and post-tests indicate a significant improvement in various aspects of soft skills and character building. Initial pre-test scores ranged from 52% to 60%, while post-training scores increased to 78% to 85%. The most significant improvements were observed in communication and leadership skills, which increased from 55% to 80% and 60% to 85%, respectively. These findings indicate that interactive and experience-based training methods are effective in shaping superior human resources ready to compete in the agribusiness workforce.